Impact of Organizational Cultur e on Organizational Effectiveness-A Study of Eastern Railway - Dey, Prajna Paromita; Parmar , Jai Singh (Gyan Management Journal, 2017)
The present study has been conducted with the purpose of examining the impact of organizational culture on organizational effectiveness in Eastern Railway. Data were gathered with the help of five point /ikert scales from 700 employees of all the divisions, workshops as well as the headquarters of Eastern Railway. The findings of the study reveal that organizational culture has a moderately strong relationship with effectiveness and is also a significant predictor of organizational effectiveness of Eastern Railway.
Keywords: Organizational Culture; Organizational Effectiveness; Eastern Railway